The Type of Honeybees Forages in District of Pakem Sleman and Nglipar Gunungkidul Yogyakarta - Agussalim Agussalim; Ali Agus; Nafiatul Umami; I Gede Suparta Budisatria (Buletin Peternakan, 2018)
This research aimed to investigate the type of plants for honeybees forages in Pakem Sleman and Nglipar Gunungkidul. This research was conducted from 16 March to 12 May 2016. The method used was direct observation in the plantations, fields, and forests. The type of plants observed were dominant plants, so can be developed beekeeping, honey. To determine the type of plants that produce nectar and pollen, one or two samples of flower in each plant were taken, then the availability of nectar and pollen was checked. The data of honeybees forage types were analyzed descriptively. The results showed that the type of honeybees forages in Pakem Sleman consisted of coconut, coffee, banana, calliandra, avocado, rice, albizia, chili, tomato, long beans, mustard green, maize, cucumber, melinjo, mahogany, cassava, and cherry. Honeybees forages in Nglipar Gunungkidul consisted of coconut, albizia, acacia, banana, peanuts, tamarind, eucalyptus, rambutan, sorghum, cacao, soybeans, cassava, maize, rice, rose wood, mahogany, and cherry. Thus, Pakem Sleman and Nglipar Gunungkidul have great potential for development of beekeeping honey.